Identification and partial characterisation of new members of the Ixodes ricinus defensin family - Tonk, Miray; Cabezas-Cruz, Alejandro; Valdés, James J; Rego, Ryan O M; Rudenko, Nataliia; Golovchenko, Maryna; Bell-Sakyi, Lesley; de la Fuente, José; Grubhoffer, Libor (Gene, 2014)
The hard-bodied tick Ixodes ricinus (castor bean tick) is the most common tick species in Europe. I. ricinus is a vector of the causative agents of diseases that affect humans and animals including tick-borne encephalitis, borreliosis, tick-borne fever and babesiosis. The innate immune system provides ticks with quite an efficient defence against some pathogenic microorganisms in the event of their penetration into the tick body or through the blood meal. Antimicrobial peptides (AMPs) constitute an important feature of the tick immune system. Defensins are a well-known class of AMPs. Members of the defensin family of proteins have been reported in several tick species. So far, only two defensins had been identified from I. ricinus. In this study, we report the identification of six novel putative defensins from I. ricinus at the genomic and transcriptional levels. At the genomic level they show differences with one being intronless, while others contain two introns. The expression pattern of these molecules in the salivary glands, midgut, ovary, Malpighian tubules, haemolymph and the tick cell line IRE/CTVM19 was determined. Some of them are tissue specific while others seem to be ubiquitous. Molecular and phylogenetic analyses show that these novel members of the I. ricinus defensin family differ phylogenetically and structurally; nevertheless, the cysteine pattern is highly conserved among the family members. Finally, antimicrobial-peptide prediction tools were used to predict putative antimicrobial activity of our defensins. They show putative antimicrobial activity mainly against Gram-positive bacteria. This study displays the diversity of the defensin family in the tick I. ricinus.
Keywords: Animals; Arthropod Proteins; Female; buněčné linie; defensiny; klíště; ženské pohlaví; morčata; Cell Line; Phylogeny; Cloning, Molecular; Sequence Analysis, DNA; Guinea Pigs; transkriptom; klonování DNA; zvířata; sekvenční analýza DNA; Transcriptome; proteiny členovců; fylogeneze; Defensins; Ixodes